Identification of Inorganic and Organic Inclusions in the Subglacial Antarctic Lake Vostok Ice with Raman Spectroscopy - Böttger, Ute; Bulat, S.; Hanke, Franziska; Pavlov, S.; Greiner-Bär, Michael; Hübers, Heinz-Wilhelm (Journal of Raman Spectroscopy, 2017)
The investigation of inclusions entrapped into the accretion ice of the subglacial Lake Vostok in Antarctica gives an insight into former times of the Antarctic history. Terrestrial (of biological and geologically-mineralogical origin) as well as extraterrestrial (meteorites) materials are hermetically embedded in the Vostok ice core and provide information about the conditions and events on Earth existed/occurred during last million years. Confocal Raman spectroscopy is well suited for the analysis of the inclusions without melting the ice and, therefore, preventing undesirable contamination with present-day material. It is a nondestructive method for material identification with depth resolving capability. It permits a locally precise statement about the chemical-mineralogical composition and allows the context information preservation of several side by side inclusions. Here, we present first results of our Raman measurements of the inclusion embedded in the Lake Vostok ice sample 5G-3 3607-4 (3607 m depth). The results obtained confirm that Raman spectroscopy is a very useful method for the exploration of inclusions entrapped into lattice of any natural ice. As Raman spectroscopy is already planned to be applied in upcoming missions in space research (ExoMars, Mars 2020, to the icy moons) a co-operation of the space science community with the Antarctica-Lake Vostok community is suggested to test the space instrumentation under the extreme environment of the Central East Antarctica and conditions of the subglacial Lake Vostok.